2015
DOI: 10.1002/tox.22196
|View full text |Cite
|
Sign up to set email alerts
|

Sesame indicum, a nutritional supplement, elicits antiamnesic effect via cholinergic pathway in scopolamine intoxicated mice

Abstract: Sesame seeds have the ability to interact with cholinergic components involved in memory function/restoration and also an interesting candidate to be considered for future cognitive research. © 2015 Wiley Periodicals, Inc. Environ Toxicol 31: 1955-1963, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Our results are in parallel with that found by [5] who declared the negative effect of high fat diet which affects oxidative stress. Same results were found by [6] who noted that high fat diet even for short duration affect potentially brain function. Sesame oil acts as magic ingredient that prevents brain damage.…”
Section: Bdc=basal Diet Control Lsd=least Significant Differencesupporting
confidence: 77%
See 2 more Smart Citations
“…Our results are in parallel with that found by [5] who declared the negative effect of high fat diet which affects oxidative stress. Same results were found by [6] who noted that high fat diet even for short duration affect potentially brain function. Sesame oil acts as magic ingredient that prevents brain damage.…”
Section: Bdc=basal Diet Control Lsd=least Significant Differencesupporting
confidence: 77%
“…Based on our previous findings, Baked cake was produced and evaluated from sesame oil (5 g sesame oil/ 30 g one serving) and fortified with orange peel as a functional food for brain injury. Chemical analysis of cake was showed in table (6) from this table it could be noticed that carbohydrate content was 42.8% while protein was 12.2% and fat 13%. Fig ( 10) statistical analysis of sensory evaluation.…”
Section: Bdc=basal Diet Control Lsd=least Significant Differencementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the SD had a positive effect and the HFD had a negative effect on memory. Some studies have demonstrated that the HFD, even for a short period of life can potentially disrupt a number of behavioral tests of learning and memory, while sesame seed extract reduced acetylcholinesterase activity and the level of BAX and caspase3 [47]. Thus, the results are inconsistent due to the differences in research designs, and length of HFD exposure during critical periods of development, speci c types of fatty acids, and gender [48].…”
Section: The Comparison Of the Levels Of Mda Tos Tac And Thiol In Dif...mentioning
confidence: 99%